1989
DOI: 10.1038/hdy.1989.25
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of laboratory reared Mytilus edulis.: II. Selection at the leucine amino peptidase (Lap) locus

Abstract: Offspring from several families and a mass mating of Mytilus edulis were cultured in the laboratory up to the juvenile stage under different temperature regimes. Mussels were genotyped at the leucine aminopeptidase (Lap) locus at the spat stage (post-metamorphosis) using cellulose acetate electrophoresis and at the juvenile stage using starch gel electrophoresis. Significant deviations from expected genotype frequencies were found in many cultures at both stages and certain genotypes were generally found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…

Laboratory cultures of offspring from single families and a mass mating of Mytilus eduIis were reared to the spat stage at different temperatures. Previous papers in this series (Beaumont et al , 1989 have demonstrated indirect selection, unrelated to salinity, at the Pgm and Gpi loci, and direct salinity-related selection at the Lap locus. Using electrophoresis, frequencies of genotypes at the Odh, Pgm, Gpi, Hex, EsD, Pgk and Dia loci were recorded at the spat stage and, again, where possible, in juveniles.

…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…

Laboratory cultures of offspring from single families and a mass mating of Mytilus eduIis were reared to the spat stage at different temperatures. Previous papers in this series (Beaumont et al , 1989 have demonstrated indirect selection, unrelated to salinity, at the Pgm and Gpi loci, and direct salinity-related selection at the Lap locus. Using electrophoresis, frequencies of genotypes at the Odh, Pgm, Gpi, Hex, EsD, Pgk and Dia loci were recorded at the spat stage and, again, where possible, in juveniles.

…”
mentioning
confidence: 72%
“…Secondly, although laboratory conditions would be expected to be "better" for mussels, than those in the wild, in the sense that no predators are present, as pointed out elsewhere (Beaumont et al 1989), one source of stress in laboratory culture may be nutrition. Microalgae were provided for larval cultures at higher densities than would normally be found in the wild, but only two species were used.…”
Section: Hexmentioning
confidence: 99%
“…Details of electrophoresis and allele nomenclature are given in Beaumont et al (1983Beaumont et al ( , 1988Beaumont et al ( , 1989Beaumont et al ( , 1990 accidental exchange of larvae between cultures and the ingress of wild larvae into juvenile rearing systems. Zouros et al (1992) also noted these constraints for genetic studies in bivalves.…”
Section: Discussionmentioning
confidence: 99%
“…( , 1988. In some families, 3-day-old veliger larvae were partitioned into several separate cultures which were reared from then on under different conditions of salinity or temperature (Beaumont et at., 1988(Beaumont et at., , 1989(Beaumont et at., , 1990; Table 1). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation